Relationship Between Serum Lipid Profiles and Carotid Intraplaque Neovascularization in a High–Stroke‐Risk Population: A Cross‐Sectional Study in China - Ying Wang (Wiley, 2021)
Background Evidence of the association between serum lipid profiles and intraplaque neovascularization (IPN) is still limited. We aimed to study the value of a novel Doppler method, superb microvascular imaging, in correlating serum lipid profiles and evidence of IPN in a population with a high risk of stroke. Methods and Results A community‐based cross‐sectional study was conducted in Beijing, China. Residents (aged ≥40 years) underwent questionnaire interviews, physical examinations, and laboratory testing in 2018 and 2019. Subjects with a high risk of stroke were then selected. Standard carotid ultrasound and carotid plaque superb microvascular imaging examinations were then performed on the high–stroke‐risk participants. Logistic regression was used to evaluate the relationship between serum lipid profiles and carotid plaque IPN. Overall, a total of 250 individuals (mean age, 67.20±8.12 years; 66.4% men) met the study inclusion criteria. Superb microvascular imaging revealed carotid plaque IPN in 96 subjects (38.4%). Subjects with IPN were more likely to be current smokers (34.0% versus 46.9%, P=0.046), and their identified carotid plaques were much thicker (2.35±0.63 mm versus 2.75±0.80 mm, P=0.001). Serum lipids, including total cholesterol, non–high‐density lipoprotein cholesterol, and low‐density lipoprotein cholesterol were positively associated with the presence of IPN (4.33±1.00 mmol/L versus 4.79±1.12 mmol/L, P=0.001; 2.96±0.92 mmol/L versus 3.40±1.01 mmol/L, P=0.001; 2.18±0.76 mmol/L versus 2.46±0.80 mmol/L, P=0.005, respectively), and after adjustment for other confounders, the positive relationship remained significant. Furthermore, non–high‐density lipoprotein cholesterol (odds ratio, 2.62 [95% CI, 1.35–5.06]) was significantly associated with the presence of carotid plaque IPN even after adjusting for low‐density lipoprotein cholesterol. Conclusions Total cholesterol, non–high‐density lipoprotein cholesterol, and low‐density lipoprotein cholesterol were positively associated with the presence of carotid IPN in a Chinese high–stroke‐risk population. Further prospective studies should be conducted to better understand how much finding IPN adds to current stroke prediction tools.